Successes and Failures of the Implementation of the Rural Development Programme 2014–2020 Measure “Agri-Environment and Climate” in Lithuania - Aistė Galnaitytė; Irena Kriščiukaitienė; Virginia Namiotko (Agriculture)
The focus on environment and climate-friendly farming is increasingly important in the European Union (EU) Common Agricultural Policy (CAP). Activities of the Measure M10 “Agri-environment and Climate” of the Rural Development Programme (RDP) 2014–2020 were those policy instruments that pursued environmental and climate goals over large areas under agricultural activities, but their effectiveness is still being questioned. After evaluating implementation successes and failures of the activities of the Measure M10 “Agri-environment and Climate” of the Lithuanian RDP 2014–2020, we aim to contribute to policy instruments that are better designed, more effective, and more attractive for farmers to achieve environmental and climate goals. This research was conducted in several stages: (1) a thorough analysis of the Measure M10 and its implementation; (2) analysis of the Measure M10 activities’ contribution to the policy target areas; (3) multi-criteria evaluation of the activities; (4) survey of beneficiaries and discussions in the focus groups. The data available from the Ministry of Agriculture of the Republic of Lithuania, Agricultural Data Center, and National Paying Agency under Ministry of Agriculture of the Republic of Lithuania was used for the analysis. Analysis of the strategic documents and data on the implementation of Measure M10 was supplemented with results from studies focused on the environmental impact of the implementation of Measure M10 in Lithuania. Multi-criteria evaluation methods were used to arrange the activities of the Measure with respect to the selected indicators. The results from the survey of beneficiaries and discussions in the focus groups let us better clarify the motives, experiences, and preferences of farmers’ participation in the activities of Measure M10. The questionnaire was distributed to 2455 beneficiaries through the National Paying Agency and 342 answers were received back, i.e., 13.9%. Five discussions in focus groups, formed from farmers participating and not participating in the activities, representatives of implementing institutions, and employees of consulting and scientific institutions, were organized. The research has revealed areas for improvement in Measure M10, and suggestions for improvement were prepared to better achieve environmental and climate objectives.